The association of interleukin-6 (−174 G/C) polymorphism with risk of chronic kidney disease and erythropoietin hyporesponsiveness - Noha Alnair Abdelrhman; Elshazali Widaa Ali (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: The plasma levels of the cytokine interleukin-6 (IL-6) have been reported to be associated with risk of chronic kidney disease (CKD) and erythropoietin (EPO) responsiveness. The G/C promoter polymorphism of IL-6 is associated with expression and levels of IL-6, so it may confer increased risk to CKD and modulate EPO responsiveness. Objectives: This study aimed to examine the association of IL-6 G/C polymorphism with risk of CKD and EPO hyporesponsiveness. Patients and Methods: A total of 40 haemodialysis patients on EPO therapy, and 30 age- and sexmatched apparently healthy volunteers as a control group were recruited for this study. Blood samples were collected from each participant and used for complete blood count (CBC) using automated haematology analyser and molecular analysis of IL-6 -174 G/C polymorphism using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: The results showed that IL-6 GG genotype is the most frequent in patients (82.5%) followed by GC genotype (17.5%), while all subjects of the control group were found to have GG genotype only. There was a statistically significant association between the polymorphism and end-stage CKD (P=0.02). Only 10% of the patients were found to achieve the target haemoglobin level. Although all of them had GG genotype, no association was found between the polymorphism and the achievement of target haemoglobin level (P=0.16). Conclusion: IL-6 G/C polymorphism is significantly associated with CKD, but not with EPO responsiveness in haemodialysis patients.